A new orphan member of the nuclear hormone receptor superfamily that interacts with a subset of retinoic acid response elements. - Myriam Baes; T Gulick; Hueng-Sik Choi; Maria‐Grazia Martinoli; Devendranath Simha; David D. Moore (1994)
We have identified and characterized a new orphan member of the nuclear hormone receptor superfamily, called MB67, which is predominantly expressed in liver. MB67 binds and transactivates the retinoic acid response elements that control expression of the retinoic acid receptor beta 2 and alcohol dehydrogenase 3 genes, both of which consist of a direct repeat hexamers related to the consensus AGGTCA, separated by 5 bp. MB67 binds these elements as a heterodimer with the 9-cis-retinoic acid receptor, RXR. However, MB67 does not bind or activate other retinoic acid response elements with alternative hexamer arrangements or any of several other wild-type and synthetic hormone response elements examined. The transactivation of retinoic acid response elements by MB67 is weaker than that conferred by the retinoic acid receptors but does not require the presence of all-trans retinoic acid, 9-cis-retinoic acid, or any exogenously added ligand. We propose that MB67 plays an important role in the complex network of proteins that govern response to retinoic acid and its metabolites.